Durability of Hepatitis B Surface Antigen Loss With Nucleotide Analogue and Peginterferon Therapy in Patients With Chronic Hepatitis B. Issue 1 (10th October 2019) - Lok, Anna S.; Zoulim, Fabien; Dusheiko, Geoffrey; Chan, Henry L.Y.; Buti, Maria; Ghany, Marc G.; Gaggar, Anuj; Yang, Jenny C.; Wu, George; Flaherty, John F.; Subramanian, G. Mani; Locarnini, Stephen; et al.
Abstract : In patients with chronic hepatitis B (CHB), loss of hepatitis B surface antigen (HBsAg) is considered a functional cure. However, HBsAg loss is uncommon with existing therapies, and predictive factors associated with HBsAg seroreversion are unknown. Using pooled data from three phase 3 clinical trials of patients with CHB treated with nucleos(t)ide analogue (NUC) monotherapy or peginterferon (Peg‐IFN) ± NUC combination therapy, we conducted a retrospective analysis to characterize patients who achieved sustained HBsAg loss, the predictors of HBsAg seroreversion, and the impact of hepatitis B surface antibody (anti‐HBs) seroconversion on durability of HBsAg loss. In these three international trials, 1, 381 adults with CHB received either NUC monotherapy for up to 10 years or Peg‐IFN‐containing regimens for up to 1 year. A total of 55 patients had confirmed HBsAg loss, defined as two or more consecutive negative‐qualitative HBsAg results, with a minimum of one repeat result after the end of treatment. Throughout a median of 96 (quartile [Q]1, Q3, 46, 135) weeks follow‐up after HBsAg loss, HBsAg loss was durable in 82% (n = 45) of patients, with 10 patients experiencing HBsAg seroreversion. Anti‐HBs seroconversion was observed during follow‐up in 78% of patients who lost HBsAg and in 60% of those who subsequently seroreverted. In analyzing predictors of HBsAg seroreversion, study treatment was significant, yet anti‐HBs seroconversion and treatment duration after initial HBsAg loss were not. Risk of HBsAg seroreversion was observed to be lower if HBsAg loss was sustained through the off‐treatment week 24 visit (8/10 seroreversions occurred by posttreatment week 24). Conclusion: HBsAg loss after NUC or Peg‐IFN‐containing regimens was durable in 82% of patients with CHB. Anti‐HBs seroconversion and treatment duration after initial HBsAg loss were not significantly associated with durability of HBsAg loss. Abstract :